Strategi Agromedicine untuk Pencegahan Fibrosis Paru pada Petani: Tinjauan Sistematis Modifikasi Alat Penyimpanan Gabah, Ventilasi Gudang, dan Efektivitas APD Respirator - Rian Hendriyana Dwi Imanta; Indri Windarti; Laisa Azka; Andreas Infianto (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Pulmonary fibrosis is a progressive respiratory disease associated with chronic inhalation of respirable dust and bioaerosols, posing a substantial occupational health risk for agricultural workers. Farmers involved in grain storage and handling are frequently exposed to organic dust, fungal spores, and endotoxins that can induce persistent alveolar inflammation and irreversible fibrotic changes. This systematic review examines agromedicine-based prevention strategies focusing on grain storage modification, warehouse ventilation, and the effectiveness of respiratory protective equipment. Evidence indicates that improved storage design and controlled ventilation systems significantly reduce airborne particulate concentrations, thereby lowering cumulative inhalation exposure. Respiratory protective devices, particularly high-efficiency respirators, provide additional individual-level protection, although their real-world effectiveness is strongly influenced by user compliance, proper fitting, and training. The findings highlight that reliance on personal protective equipment alone is insufficient to prevent long-term pulmonary damage. An integrated prevention framework combining engineering controls, environmental management, and occupational health education is essential to reduce the burden of pulmonary fibrosis among farmers and promote sustainable agricultural health practices.